Transitional justice standards on reparations for women subjected to violence in the CEDAW Committee’s evolving legal practice - Rubio-Marín, Ruth (International journal of transitional justice, 2020)
Violence against women continues to be one of the most pressing global concerns. Reparations for women victims of violence have been addressed by the Convention on the Elimination of All Forms of Discrimination against Women Committee over the last 15 years. This article critically examines the evolving practice of the Committee on reparations, in light of the transitional justice doctrinal and normative acquis on gender-sensitive reparations. We systematize legal interpretations, identify trends and milestones, and link them to transitional justice elements. We also suggest that the transitional justice reparations framework can be, and is in fact being, applied to non-transitional contexts, independent of armed conflict and authoritarian regimes. Further, we propose recommendations for the Committee to engage in a more explicit ‘dialogue’ with these ongoing developments to the benefit of women in their everyday lives and in recognition of the structural dimension of violence against women, even in what are other so-called peaceful and stable societies.